Species differences in ligand interaction and activation of estrogen receptors in fish and human. Issue 195 (December 2019) - Asnake, Solomon; Modig, Carina; Olsson, Per-Erik
Graphical abstract: Highlights: ER ligands show species differences in binding potencies. Ligand-receptor interactions are affected by LBP volume and flexibility. Species specific residues contribute to docking scores for ER ligands. Combining in vitro and in silico data increases insight into ER responsiveness. Abstract: Estrogen receptor (ER) sequences vary between species and this suggests that there are differences in the ligand-specificity, leading to species-specific effects. This would indicate that it is not possible to generalize effects across species. In this study, we investigated the differences in activation potencies and binding affinities of ER´s alpha (α) and beta (β) in human, zebrafish and sea bream to elucidate species differences in response to estradiol, estrone, estriol and methyltestosterone. In vitro analysis showed that estradiol had the highest activity for all the ER´s except for human ERβ and seabream ERβ2. Alignment of the ligand binding domain and ligand binding pocket (LBP) residues of the three species showed that different residues were involved in the LBPs which led to differences in pocket volume, affected binding affinity and orientation of the ligands. By combining in silico and in vitro results, it was possible to identify the ligand specificities of ER´s. The results demonstrated that the human ER´s show lower resolution in ligand-dependent activation, suggesting higher promiscuity, than the zebrafish and seabream ER´s. These results show species-specificity of ER´s and suggest that species-specific differences must be taken into consideration when studying different exposure scenarios.